Cameroon Grassfields Civilization. - Warnier, Jean-Pierre (Langaa RPCIG, 2012)
This book brings and blends together a dozen scholarly articles published by the author since the 1970s. It sketches two different yet related stories: first, that of one of the most ancient and prestigious African civilizations, the antiquity and sophistication of which are becoming more and more prominent as field research unfolds their many facets. Second, the story of the researcher himself, who has had to alter and shift his approach to that civilization as he got to meet Grassfielders, colleagues, friends and scholars who changed his views about the Grassfields kingdoms and their people.